2012
DOI: 10.1021/cs2006873
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic H2O2 Production from Ethanol/O2 System Using TiO2 Loaded with Au–Ag Bimetallic Alloy Nanoparticles

Abstract: TiO2 loaded with Au–Ag bimetallic alloy particles efficiently produces H2O2 from an O2-saturated ethanol/water mixture under UV irradiation. This is achieved via the double effects created by the alloy particles. One is the efficient photocatalytic reduction of O2 on the Au atoms promoting enhanced H2O2 formation, due to the efficient separation of photoformed electron–hole pairs at the alloy/TiO2 heterojunction. Second is the suppressed photocatalytic decomposition of formed H2O2 due to the decreased adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
254
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(283 citation statements)
references
References 32 publications
(62 reference statements)
12
254
3
6
Order By: Relevance
“…This was potentially ascribed to the smaller size of Au nanoparticles in the Au/C 3 N 4 -500(N 2 ) (Figure 1). Similar findings were also observed in the Au-and AuAg-loaded TiO 2 photocatalytsts [14,16]. The apparent quantum yield (Φ AQY ) for H 2 O 2 formation over the Au/C 3 N 4 -500(N 2 ) was calculated using the equation…”
Section: Photosynthesis Of H 2 Osupporting
confidence: 67%
See 2 more Smart Citations
“…This was potentially ascribed to the smaller size of Au nanoparticles in the Au/C 3 N 4 -500(N 2 ) (Figure 1). Similar findings were also observed in the Au-and AuAg-loaded TiO 2 photocatalytsts [14,16]. The apparent quantum yield (Φ AQY ) for H 2 O 2 formation over the Au/C 3 N 4 -500(N 2 ) was calculated using the equation…”
Section: Photosynthesis Of H 2 Osupporting
confidence: 67%
“…In such a process, a highly efficient photocatalyst could be a core factor in order to direct the synthesis of H 2 O 2 . Titanium dioxide (TiO 2 ), a widely studied photocatalyst, has been found to enable the formation of H 2 O 2 [12][13][14][15][16]. Several strategies have been developed to enhance the H 2 O 2 yield on TiO 2 -based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of supported Au-Ag and Au-Cu bimetallic catalysts usually involves two kinds of protocols: (a) preformation of bimetallic nanoparticles in solution followed by deposition on a certain support [57], and (b) deposition of two metal precursors on a support followed by co-reduction or sequential reduction [21,58]. In the first protocol, both the chemical composition and the particle size, and even the particle shape, can be controlled well by taking full advantage of solution-based synthesis of colloidal metals [53].…”
Section: One-pot Methodsmentioning
confidence: 99%
“…Bimetallic alloy particles loaded on TiO2 are effective for other photocatalytic reaction. Recently, we found that P25 TiO2 loaded with Au _ Ag bimetallic alloy particles efficiently catalyzes the formation of hydrogen peroxide under UV irradiation in alcohol solution with O2 41) . …”
Section: Loading Of Metal Nanoparticles On Tio2 Surfacementioning
confidence: 99%